2019
DOI: 10.1002/dvdy.69
|View full text |Cite
|
Sign up to set email alerts
|

A novel conserved enhancer at zebrafish zic3 and zic6 loci drives neural expression

Abstract: Background Identifying enhancers and deciphering their putative roles represent a major step to better understand the mechanism of metazoan gene regulation, development, and the role of regulatory elements in disease. Comparative genomics and transgenic assays have been used with some success to identify critical regions that are involved in regulating the spatiotemporal expression of genes during embryogenesis. Results We identified two novel tetrapod‐teleost conserved noncoding elements within the vicinity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Specifically, tissue-specific gene expression patterns necessitate the presence of long-range regulatory regions, which are often referred to as enhancers. These enhancers are responsible for finely tuning the spatial, temporal, and dosage-dependent expression of target genes [106], thereby ensuring the precise and coordinated formation of pacemaker tissues within the heart. Elucidating the function and interactions of these cis-regulatory modules is crucial for unraveling the complexities of CCS development, as well as paving the way toward understanding the underlying molecular mechanisms that govern its expression and function.…”
Section: The Genetic Network Of Ccs Developmentmentioning
confidence: 99%
“…Specifically, tissue-specific gene expression patterns necessitate the presence of long-range regulatory regions, which are often referred to as enhancers. These enhancers are responsible for finely tuning the spatial, temporal, and dosage-dependent expression of target genes [106], thereby ensuring the precise and coordinated formation of pacemaker tissues within the heart. Elucidating the function and interactions of these cis-regulatory modules is crucial for unraveling the complexities of CCS development, as well as paving the way toward understanding the underlying molecular mechanisms that govern its expression and function.…”
Section: The Genetic Network Of Ccs Developmentmentioning
confidence: 99%
“…For better understanding of such GRNs, the identification of cis-regulatory modules involved in the development of the cardiac conduction system will pave the way to elucidate molecular mechanisms underlying their regulation of expression. Tissue-specific gene expression obliges longrange regulatory regions, such as enhancers, which dictate the precisely spatial-temporal and dosagedependent expression of their target genes (Minhas et al, 2019). The availability of publicly available genomics data, well-established protocols for chromosomal conformation capture followed by nextgeneration sequencing in isolated hearts (3C, 4C-Seq, 5C, Hi-Seq), or derived methods like FAIRE-Seq and ATAC-Seq, single-cell sequencing, multiple genome-wide Chip-seq datasets and evolutionary conservation studies across various vertebrate model species (for example mice, chicken or zebrafish) can identify multiple regulatory landscapes which act as cardiac conduction-specific enhancers (Moskowitz et al, 2007).…”
Section: The Genetic Network Of Ccs Developmentmentioning
confidence: 99%
“…This observation led us to speculate that additional cis ‐acting elements might be in place to regulate spatiotemporal Gli3 expression. Previous attempts for Gli3 enhancer discovery made use of fugu and zebrafish genomes (as teleost representatives) to define evolutionary conserved enhancers in intronic and intergenic intervals of the human GLI3 gene (Minhas et al, 2019; Parker et al, 2011). It has been reported that a large subset of mammalian tissue‐specific enhancers might not be detected by direct mammalian–zebrafish/fugu comparisons, presumably due to large‐scale duplications and rapid evolution of these representative teleost genomes (Braasch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%